Development of the plant encyclopedia used in traditional foods of sekadau regency - Rini, Rini; Sunandar, Ari; Rahayu, Hanum Mukti (JURNAL BIOEDUKATIKA, 2024)
Utilization of plants as food ingredients represents local wisdom and cultural richness that needs to be preserved. Preservation of this knowledge can be achieved through educational media. This research aims to produce valid learning media and measure positive responses from students. It follows the Research and Development (R&D) approach using the ADDIE development model consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Instruments used include observation sheets, interview sheets, questionnaires, and validation sheets. Validation results from subject matter experts achieved 87.58% (very valid), media experts 96.66% (very valid), and language experts 89.99% (very valid). Students responded very positively in small-scale trials with 89.1% and large-scale trials with 93.7%. The research results indicate that the plant encyclopedia used in the traditional cuisine of Sekadau District is suitable for learning and receives positive feedback from students.